Photorealism in Low-cost Virtual Reality Devices - Cataldo Junior, Wellingston; Pereira, Lidiane; Moreno, Marcelo; Silva, Rodrigo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
This paper presents a novel framework that allows low-cost devices to visualize and interact with photorealistic scenes. To accomplish this task, we use the Unity streaming package that allows for streaming an application within its editor and the Unity's high definition render pipeline that has a proprietary ray-tracing algorithm. The framework contains a realistic scene using a ray tracing algorithm, a virtual reality camera with barrel shaders to correct the lens distortion necessary to use low-cost cardboards, and a method to collect the mobile device's spatial orientation through a browser to control the user's vision delivered via WebRTC. The proposed framework can produce low-latency, realistic, immersive environments to be accessed through low-cost HMDs and inexpensive mobile devices.